Physeter macrocephalus Linnaeus 1758 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Physeter macrocephalus Linnaeus, 1758. Syst. Nat., 10th ed„ 1:76. TYPE LOCALITY: Netherlands, Middenpiat. DISTRIBUTION: Northern Hemisphere, tropical to subarctic waters, Southern Hemisphere, all seas. COMMENT: Neotype designated by Husson and Holthuis, 1974, Zool. Meded., 48(19):212. Linnaeus used both catodon and macrocephalus in the 10th edition. P. catodon has line priority. In addition, catodon is described as "fistula in rostro" (blowholes on the nose), which is correct, and is the only diagnostic character in the description that will separate the sperm whale from all other whales. P. macrocephalus, however, is described as "fistula in cervice" (blowholes on the neck), which is incorrect, and is the same as all other whales (DWR). See Hershkovitz, 1966, for additional discussion; but also see Rice, 1977:11; and Husson and Holthuis, 1974, Zool. Meded., 48(1 9):205-217. PROTECTED STATUS: CITES - Appendix I and U.S. ESA - Endangered as P. catodon (— macrocephalus). ISIS NUMBER: 5301411004002001001 as P. catodon. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Cetacea, pp. 290-304 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 299, DOI: 10.5281/zenodo.7352983